The Use of The Expression Tabe’ to Show Politeness in Toraja Language Short Talks - Britni Delfita Pata’ Allo K; Dewi Nuryanti (ESENSI LINGUA, 2022)
This research was aimed to explain the purpose of using the expression tabe’ in Toraja language. The data was taken from the short talks between two people, it was recorded data. The writer used the theory by Penelope Brown about politeness. The result of the analysis found five reasons for a speaker using tabe’; to make a request for something; 2) to permit something; 3) to show regret; 4) to apologize for making a mistake; and 5) to stress the information about one thing.